Translocation of the tetracycline resistance determinant from R100-1 to the Escherichia coli K12 chromosome - FOSTER, TIMOTHY (My University, 1975)
Pairs of normally incompatible derivatives of R100-1 (one ChlS TetR, the other ChilR TetS) were forced to coexist in a recA host by selection for ChlR TetR cells. After many generations stable derivatives were isolated. The analysis of none independent stabilization experiments showed that in each case TetR was translocated from the plasmid to the chromosome of the host. No evidence for the joint integration of other plasmid genes (those controlling transfer, antibiotic resistance, incompatibility, or origin of transfer replication) was obtained. One of the chromosomal TetR determinants was mapped close to metE.